Creating ourselves: works from the ISelf Collection : the self in art - Butler, Emily; Stobbs, Candy; Whitechapel Art Gallery. (Whitechapel Gallery, 2017)
"From Surrealist selfies to feminist self-portraiture, the ISelf Collection explores identity and the human condition through the central themes of birth, death, sexuality, love, pain and joy. Taking the display of the collection at Whitechapel Gallery as its springboard, this book looks generally at the question of the self in modern and contemporary art, and the ways in which artists are thinking about being and identity as an individual, in relation to others, to society and the wider world. Featuring works by a world-class roster of artists including Francis Alys, Fiona Banner, Lynda Benglis, Louise Bourgeois, Tracey Emin, Alex Katz, Sarah Lucas, Mike Nelson, Cindy Sherman, John Stezaker and Wolfgang Tillmans, this fully illustrated catalogue also includes essays by Glenn Adamson, Frances Borzello, Nicholas Cullinan and Amelia Jones, as well as a selection of quotes by influential writers and theorists as chosen by some of the artists included."
Keywords: arts; arts visuels et médiatiques; corps; cours; discipline; har4600; identités; premier cycle; thématiques